Brave new world greatest hits - Azmi Sharom (Strategic Information and Research Development Centre, 2015)
Azmi Sharom may be best known for his law expertise and his intimate acquaintance with the Sedition Act, but as this collection shows, he has a lot more to talk about: faith, fear-mongering, football, and Flight of the Hamsters, for example. Drawn from selected newspaper columns published between 2007 and 2015, these essays cover Merdeka, mob rule, and the path from one to the other. Azmi clears up the question of whether Malaysia is a secular or Islamic state, explains the role of the monarchy as determined by the Constitution, and outlines (perhaps a little wearily) how the introduction of simple concepts such as academic freedom and an independent police commission might actually be beneficial to everybody. Along the way, we're invited to consider how history is taught to our youth, who's responsible for landslides, and why we can't all just unite against our common enemy, the Aedes mosquito. The state of Malaysia today ensures that he's never short of material, and he's often scathing, frequently hilarious and consistently fair in his assessment of it. The book comes with a free CD of two original songs by Azmi. Azmi Sharom is an Associate Professor in a public university. He teaches Human Rights and Environmental Law. He has been writing articles for newspapers and magazines for many years, starting with comic reviews in the 90s and moving onto current affairs on an ad hoc basis from 2001 and then regularly from 2007. Currently he has regular columns in The Star and Sin Chew Jit Poh